Elevated serum neurofilament light chain levels in patients with neuropsychiatric systemic lupus erythematosus: a cross-sectional study - Karel Pavelka; Marta Olejárova; Veronika Balajková; Aneta Prokopcová; Martin Elisak; Hana Mojžišová (Lupus Science and Medicine)
Background The neurofilament light chain (NfL) in cerebrospinal fluid (CSF) and serum as a marker of neuronal damage may be a potential biomarker of neuropsychiatric involvement in SLE (NPSLE).Methods 80 patients with SLE were included.We obtained paired serum and CSF samples from 48 patients (NPSLE n=32, non-NPSLE n=16) and 31 controls. The serum and CSF levels of NfL were determined using ELISA.Results Patients with NPSLE demonstrated significantly higher levels of serum NfL compared with the non-NPSLE group (mean 31.68±36.63 pg/mL vs mean 16.75±12.48 pg/mL, respectively, p<0.05) and with controls (mean 10.74±4.36 pg/mL, p<0.01). Notably, CSF NfL concentrations in patients with NPSLE showed an upward trend (mean 1600±2852 pg/mL) in contrast to non-NPSLE patients (mean 393.4±191.9 pg/mL) and controls (mean 509.7±358.5 pg/mL). Furthermore, a positive correlation was observed between serum and CSF NfL levels in patients with NPSLE (R=0.8686, p<0.01). Elevated serum triacylglycerol concentrations, C reactive protein and organ damage were linked to increased serum (p=0.002; p<0.001; p=0.036) and CSF (p=0.008; p=0.007; p<0.001) NfL concentrations. In addition, we established a significant correlation between intrathecal NfL concentrations and interleukin-6 levels in the CSF of patients with NPSLE (R=0.5118, p<0.05).Conclusion The serum NfL levels may be a readily available marker of neuropsychiatric involvement in SLE.